FILSAFAT POLITIK ALI ABDUL RAZIQ - Rido Putra; Rido Putra (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2019)
Ali Abdul Raziq is a controversial Islamic thinker, especially when he put forward the concept of a secular state. Ali Abdul Raziq’s secularism which emphasizes the totality of his teachings is a political thought that deserves further study to find out the strengths and weaknesses of the arguments put forward by these Islamic political thinkers. According to Ali Abdul Raziq, the reality of Islamic history does not provide the necessity for a form of political organization called the khilafah and its leader to be called the caliph. The ideal state according to Ali Abdul Raziq is a country based on universal humanism that fights for its people, democracy and social justice, namely a secular state for Muslims and non-Muslims who live in the country.